PENGARUH DISKUSI REVIEW KERTAS KERJA AUDIT TERHADAP MOTIVASI DAN KINERJA AUDITOR PADA KAP DI SEMARANG - Monika Averina; Ranto P Sihombing (Universitas Katolik Soegijapranata Semarang, 2013)
Discussion of paper review audit working paper is feedback that aims to ascertain whether the audit process has been followed Public Accountants Professional Standards (SPAP) are generally accepted. It also can improve the understanding of the auditors relating to the audit work paper-making process because through the process of discussion, reviewers can clarify questions, add information and evidence related to the work during the paper making process, so as to produce a quality audit working papers. This study aims to examine the influence of audit working paper review the discussion of the performance auditor auditor through motivation as an intervening variable. Data were obtained by distributing questionnaires in registered public accounting firm in 2012 in Semarang. This research used purposive sampling Judgement, and was obtained samples 35 respondents and technique analysis used regression testing. The results of this study indicate that proposed research hypothesis is accepted.